A omissão do Estado e a construção de políticas públicas voltadas às comunidades quilombolas Kalunga: um estudo sobre as desigualdades raciais e sociais - Silva, Jeronilson Quirino da (2025)
The dissertation aims to investigate and better understand the reality of the Kalunga quilombola communities, as well as the role of the State and the development of public policies targeted at these communities. In this regard, I seek to identify the possible reasons behind the high levels of social vulnerability recurrent in this territory, addressing both the availability and the evident absence of public policies for the community as a whole, considering the persistent social vulnerability indices in the region. Two central questions guide this investigation: the first is to highlight why social inequality exists. The second, which is directly connected to the first, concerns why public policies fail to reach these localities. The research aims to examine and understand the processes involved in decision-making and agenda-setting for the formulation and implementation of public policies. This is based on three key elements: a) The formulation of public policies, such as those related to health, education, transportation, and sanitation, specifically aimed at these communities; b) The observation of the implementation processes of other public policies for the Kalunga communities (if they exist); c) The analysis of decision-making processes by municipal and state public administrators regarding the implementation of public policies in traditional communities, in response to the demands raised by the communities themselves. Thus, this is a qualitative research study supported by a case study approach, based on documents and legislation related to the studied topic.